Macroparasites and their communities of the European eel Anguilla anguilla (Linnaeus) in the Czech Republic - Moravec, František; Scholz, Tomáš (Folia parasitologica, 2015)
This paper summarises the results of parasitological examinations of the European eel Anguilla anguilla (Linnaeus) in the Czech Republic, carried out at the Institute of Parasitology, Czech Academy of Sciences (previously the Czechoslovak Academy of Sciences) within the period of 50 years (1958-2008). Even though this survey is limited to the Czech Republic, it provides extensive data probably incomparable with any other study anywhere regarding the number of eels examined and parasites found. A total of 723 eels was examined from 42 localities that belong to all of the three main river drainage systems in the country, i.e. the Elbe, Danube and Oder river basins. Of the 31 species of adult and larval macroparasites including Monogenea (4 species), Trematoda (3), Cestoda (3), Nematoda (11), Acanthocephala (5), Hirudinea (1), Bivalvia (1), Copepoda (1), Branchiura (1) and Acariformes (1), most of them (30) were recorded from the Elbe River basin. These parasites can be divided into three main groups regarding their host specificity: parasites specific for eels (26%), non-specific adult parasites occurring also in other fishes (61%) and non-specific larvae (13%). The highest number (19) of parasite species was recorded in the Mácha Lake fishpond system in northern Bohemia. The parasite communities in eels from the individual localities exhibited large differences in their species composition and diversity depending on local ecological conditions. The parasite fauna of A. anguilla in the Czech Republic is compared with that in other European countries. The nematode Cucullanus egyptae Abdel-Ghaffar, Bashtar, Abdel-Gaber, Morsy, Mehlhorn, Al Quraishy et Mohammed, 2014 is designated as a species inquirenda.
Keywords: Parasites; Host Specificity; Acanthocephala; Česká republika; Statistics as Topic; Trematoda; biodiverzita; Anguilla; Biodiversity; paraziti; Rivers; statistika jako téma; Cestoda; Czech Republic; řeky; hostitelská specificita